The Effect of Administration of Solanum Lycopersium Var Cerasiforme on Changes in Blood Pressure in Hypertension Patients - Dadi Hamdani; Andan Firmansyah; Henri Setiawan (UIMA Press, 2024)
Background : Hypertension is still a problem for some people because treatment must be carried out regularly and requires regular visits to health facilities. This is a problem for some groups of society, along with the continued use of drugs that have side effects that they must consume with long-term use. Hypertension occurs when systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg. Apart from medicines, we can also treat high blood pressure by using natural ingredients such as tomato juice. Tomato juice contains potassium and lycopene, which can lower blood pressure. Objectives : To determine the effect of giving tomato juice on changes in blood pressure in hypertensive patients. Methods : Quantitative research with a quasi-experimental design using a non-randomized control group pretest-posttest approach and a sampling technique using purposive sampling. The total sample was 62 respondents. Wilcoxon test and Mann-Whitney test were used for statistical tests. Results : Wilcoxon test results for systolic and diastolic blood pressure in the intervention group were recorded for each p-value <0.05 before and after the intervention. The results of the Mann-Whitney test for systolic and diastolic blood pressure after intervention showed a p-value <0.05. Conclusion : Giving tomato juice (Solanum lycopersicum) affects changes in blood pressure in hypertensive patients, so it is recommended as an alternative non-pharmacological treatment option.